Modern construction envelopes - Watts, Andrew 1957-; SpringerLink (Online service). (New York Springer, 2011)
Andrew Watts is an architect and facade specialist with 25 years' experience of working on major projects from the Institut du Monde Arabe and the Triangle des Gares at Euralilie for Jean Nouvel, to Federation Square for LAB, and the Millennium Bridge, London for Foster and Partners. He has a Masters Degree In Interdisciplinary Design from Cambridge University, where he developed a keen interest in the interface of structural and environmental design and architectural expression. Alongside Yasmin Watts, Andrew leads Newtecnic, facade designers for innovative arid technically complex projects around the world, collaborating with both leading architecture firms and leading contractors. The firm's work can be seen at www.newtecnic.com where a range of building types is under development. --Book Jacket.
Metal walls -- Glass walls -- Concrete walls -- Masonry walls -- Plastic walls -- Timber walls -- Metal roofs -- Glass roofs -- Concrete roofs -- Timber roofs -- Plastic roofs -- Fabric roofs.
"Newtecnic, facade architecture+technology"--Cover.
Electronic reproduction.
Keywords: Facades -- Design and construction; Walls -- Design and construction; Roofs -- Design and construction; Electronic books